Management of alcohol withdrawal syndrome (AWS) - Ćwikła, Piotr; Machała-Ćwikła, Ewelina; Szeląg, Kacper; Zdziebło, Piotr; Machała, Dominika; Łapińska, Urszula; Kujawski, Antoni; Machała, Kamila (Quality in Sport, 2024)
Alcohol withdrawal syndrome (AWS) is a complex set of symptoms that occur in alcohol-dependent individuals after sudden withdrawal or a significant reduction in alcohol consumption. AWS symptoms occur in about 50% of alcohol abusers. These symptoms may include restlessness, tremor, nausea, nervousness, tachycardia, elevated blood pressure, hyperhidrosis, insomnia, hyperactivity, and hallucinations. In some cases, seizures may occur and delirium tremens may develop, which is life-threatening and an absolute indication for hospitalization of the patient. Effective treatment of AWS is the key to prevent complications and to reduce the risk of death. Treatment of alcohol withdrawal syndrome requires a complex approach that combines properly performed diagnosis, careful monitoring of the patient’s condition, pharmacotherapy, equalization of electrolyte disorders, adequate hydration of the patient, supplementation of thiamine deficiencies and, in the case of symptoms of alcoholic delirium, intensive medical care. Pharmacological treatment plays a key role, with the first line of treatment being benzodiazepines, which reduce the risk of epileptic seizures and delirium tremens, and reduce mortality in the course of AWS. Individualized therapy adjustment and patient monitoring are crucial to ensure effective and safe treatment.